Slipped Capital Femoral Epiphysis: Diagnosis and Management - Peck, David, MD (American family physician, 2010)
Slipped capital femoral epiphysis is the most common hip disorder in adolescents, and it has a prevalence of 10.8 cases per 100,000 children. It usually occurs in children eight to 15 years of age, and it is one of the most commonly missed diagnoses in children. Slipped capital femoral epiphysis is classified as stable or unstable based on the stability of the physis. The condition is associated with obesity and growth surges, and it is occasionally associated with endocrine disorders such as hypothyroidism, growth hormone supplementation, hypogonadism, and panhypopituitarism. Patients usually present with limping and poorly localized pain in the hip, groin, thigh, or knee. Diagnosis is confirmed by bilateral hip radiography, which needs to include anteroposterior and frog-leg lateral views in patients with stable slipped capital femoral epiphysis, and anteroposterior and cross-table lateral views in patients with the unstable form. The goals of treatment are to prevent slip progression and avoid complications such as avascular necrosis and chondrolysis. Stable slipped capital femoral epiphysis is usually treated using in situ screw fixation. Treatment of unstable slipped capital femoral epiphysis usually involves in situ fixation, but there is controversy about the timing of surgery, value of reduction, and whether traction should be used.